Pancasila As A Development Paradigm - Muhammad Yogi Triyadi; Widia Anggelina; masduki asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This paper is to formulate a conceptual perspective on the reconstruction of the paradigm of the development of the rule of law in Indonesia. Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that